The Effects of islamic branding, product quality, and lifestyle to interest of skincare product purchase to Millenial Generation in Kudus Regency - Kusuma, Aryanti Muhtar; Hikmah, Maulida Ainul; Marom, Aufarul (Universitas Islam Negeri Sunan Kudus, 2020)
AbstractSkincare products become one of beauty products need for increasing beauty and facial health. Needs in fulfiling facial care including economic treatment change on Millenial Generation. Bassed on fenomenon, this research is aimed to know islamic branding, product quality, and lifestyle to interest of skincare product purchase to Millenial Generation in Kudus Regency. Analysing methode use is kuantitatife research with multiple linier regression technique using SPSS’16. Sampling used is non probability sampling and purposive sampling. Research result shows that Islamic branding has signifcant influence to purchase of skincare product, products quality have signifcant influence to purchase of skincare product, and lifestyle has signifcant influence to purchase of skincare products.Keywords: Islamic Branding, Product Quality, Lifestyle, Purchase Interest, Skincare Product, Millenial Generation